2013
DOI: 10.1001/jamainternmed.2013.563
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Quality of Life in Acute Venous Thrombosis

Abstract: Importance: Future funding for new treatments in venous thromboembolism will be guided by cost-utility analyses. There is little available information on the utility of acute venous thromboembolism, limiting the validity of economic analyses. Objective: To measure the quality of life in the health states relating to thromboembolism cost-utility analyses. Design: A prospective cohort study. Setting: A single-center, university-affiliated thrombosis clinic. Participants: Two hundred sixteen thrombosis clinic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 19 publications
0
56
1
2
Order By: Relevance
“…Instead, we used the value of -0.190 reported by Hogg et al 184 This study was conducted A length of 1 week was applied to disutilities, in line with the approach used in the study by Freeman et al, 143 in which expert opinion indicated durations of a maximum of 7 days for grade 3/4 AEs. Freeman et al 143 state that this was broadly similar to the length of stay associated with AEs reported in Twelves et al 185 Some AEs may persist for > 7 days but with reduced severity and, in this analysis, grade 1/2 AEs were assumed to have no disutility.…”
Section: Disutilities For Adverse Eventsmentioning
confidence: 99%
“…Instead, we used the value of -0.190 reported by Hogg et al 184 This study was conducted A length of 1 week was applied to disutilities, in line with the approach used in the study by Freeman et al, 143 in which expert opinion indicated durations of a maximum of 7 days for grade 3/4 AEs. Freeman et al 143 state that this was broadly similar to the length of stay associated with AEs reported in Twelves et al 185 Some AEs may persist for > 7 days but with reduced severity and, in this analysis, grade 1/2 AEs were assumed to have no disutility.…”
Section: Disutilities For Adverse Eventsmentioning
confidence: 99%
“…For example, a patient experiencing a CRNM bleeding event would have a disutility value of 0.09 subtracted from his/her baseline utility value. The disutility values for recurrent DVT, recurrent PE, non-ICH major bleeds and CRNM bleeds were obtained from previously published studies and VTE models [14][15][16][17][18] (Table 4).…”
Section: Utility and Disutility Valuesmentioning
confidence: 99%
“…La aparición de una hemorragia intracraneal o HPTEC se asoció con valores de utilidad de 0,330 [27] y 0,650 [28], respectivamente. Se consideraron también decrementos de utilidad asociados al desarrollo de eventos clínicos y sangrados, así como a la vía de administración del tratamiento anticoagulante, con un mayor impacto de la vía parenteral en la CVRS (Tabla 2) [27,[29][30][31][32][33].…”
Section: Medición Del Valor De Utilidad Asociado Con Los Fármacos En unclassified